ENVIRONMENTAL TAX AND TARIFFS UNDER THE INTERNATIONAL TRADE OF PRODUCTS. Issue 3 (4th September 2014) - Kawasaki, Akio; Ohno, Tadahisa
<x xml:space="preserve">Abstract</x> Cross‐border consumption has become more popular, prompting a growing interest in the problems related to international trade. At the same time, trans‐boundary air pollution has become a major environmental problem, meriting increased attention in environmental economics literature. This study considers these problems in the context of environmental taxes and tariffs (or customs duties on imports), assuming quadratic environmental damage. We compare the environmental tax rate with and without a tariff and demonstrate that the former is lower than the latter. We then compare the level of social welfare with and without a tariff and demonstrate that when the degree of trans‐boundary air pollution is low (high), welfare without the tariff is higher (lower) than with it. Thus, a tariff is not always necessary from the viewpoint of social welfare.